Performance Analysis of Pedestrian Paths in The Colonial Historical Area of Kota Lama Cirebon - Mira Lestira Hariani; Arni Muslimah Handayani Widjaja; Martinus Agus Sugiyanto; Ohan Farhan; Fathur Rohman (Journal of Green Science and Technology, 2023)
Pedestrian path conditions are one of the factors that affect willingness to walk and play an important role in supporting historical tourism activities. This study analyzes the performance of pedestrian paths expressed by Pedestrian Level of Service (PLOS) in the colonial historical area of Kota Lama Cirebon.  The method used in this study was to conduct a geometric survey of pedestrian paths, pedestrian flow surveys, and pedestrian travel time surveys in 10 segments scattered throughout the study area. The survey results were analyzed regarding the 1985 Highway Capacity Manual (HCM) and PLOS values generated based on available walking space. The study shows that in terms of walking space availability, most of the segments in the study area have a PLOS A score, which means they are performing well. In comparison, some segments have poor PLOS, such as Merdeka Street, Yos Sudarso Street, TJ Street, and Kebumen Street, due to the unavailability of sufficient walking paths to serve pedestrians or the presence of side obstacles that reduce the effective width of the pedestrian path. To overcome these problems, several things need to be done, such as: 1) issue a policy prohibiting selling on pedestrian paths to reduce side obstacles so that the effective width of the pedestrian path can increase; 2) widen the pedestrian path at least according to the applicable standards; and 3) provide pedestrian paths on segments that do not yet have pedestrian paths.